Afrotropical ants of the ponerine genera Centromyrmex Mayr, Promyopias Santschi gen. rev. and Feroponera gen. n., with a revised key to genera of African Ponerinae (Hymenoptera: Formicidae) - Bolton, Barry; Fisher, Brian L. (Zootaxa, 2008)
The ponerine ant genus Centromyrmex Mayr is redefined and its Afrotropical species are fully revised. Ten Afrotropical species are recognised of which six are described as new (decessor, ereptor, fugator, praedator, raptor, secutor). Two former infraspecific names are elevated to species rank (angolensis, longiventris) and four new junior synonyms of sellaris (= arnoldi, = congolensis, = constanciae, = guineensis) are established. The monotypic genus Promyopias Santschi is revived from synonymy and a new monotypic genus, Feroponera, type-species F. ferox sp. n., is introduced. The possibility of a Centromyrmex genus group is discussed and a revised key to Afrotropical genera of Ponerinae is presented.